Automatic Annual Improvement Provisions - Backman, Jules; Gitlow, A. L. (The Review of Economics and Statistics, 1950)
ONE of the outstanding developments in collective bargaining in I948 was the General Motors contract with the United Automobile Workers.' Two phases of this contract led to considerable discussion: (a) the cost of living adjustment clause and (b) the annual improvement factor for each of the two years for which the contract was drawn. Cost of living clauses are not unique in labor contracts.2 The inclusion of an annual improvement factor in the collective bargaining contract, however, did represent a significant departure from past practice. Under the General Motors' formula, provision was made for an annual improvement factor of 3 cents an hour in I948 and an increase of the same amount in May I949, in addition to adjustments required to meet changes in living costs. Since at the time the contract was signed, the average hourly rate for General Motors was about $1.50, the rate of improvement provided was about 2 per cent a year. The General Motors' rate of increase apparently was based on the long-term national average increases in output per man-hour.